SOCIAL, ECONOMIC AND ACCOUNTING SUMMARY OF THE GREEK AGRICULTURAL SECTOR 1950-2010: CENTRAL GREECE REGION - Michail Th. PAPAILIAS (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
Usually, the analysis of the economic and social development of a country or a region can be achieved either by using macroeconomic theories, or through a microeconomic approach (Sakellaropoulos, 1993). The innovation of this paper lies in the use of accounting techniques for capturing the relevant developments and in the fact that there are no similar studies in the Greek bibliography, except some fragmentary approaches of the 1950’s (Euelpides, 1953). Specifically, the objective of this article is the presentation of the social and economic development in a major region in Greece with the use of accounting statements. For this purpose the balance sheets and the income statements of the specific region were estimated per decade throughout the postwar period and the social-economic facts are tried to associate with the figures.The article is structured in three parts. The first refers to the methodology of the research. In the second, balance sheets and profit/loss accounts are presented in detail with the use of financial statement analysis methods and are attempted to correlate with the social-economic incidents. In the third the findings are evaluated.